Experiências formativas com o pensamento computacional no Brasil - Lucena, Simone (2022)
In contemporary society, connected in a network, where everyone can be transmitters and receivers of information, and where everyday devices are programmable, intelligent, and communicate with each other, it is essential to stimulate criticality in children and young people, creativity, and algorithmic reasoning for formulating and solving problems, so that they can explore the potential of the network and the objects connected to it, understanding its operation and also allowing its programming. Computational thinking thus emerges as a possibility to formulate and solve problems, allowing citizens to interact with machines, programming them, to perform tasks. This article aims to present the experiences of ECult/UFS/CNPq in training processes with high school students and basic education teachers for the development of computational thinking through plugged-in activities. These experiences reflect the research group's perspective of thinking and doing training processes with teachers in initial and continuous training for the development of computational thinking with plugged and/or unplugged activities in Brazil.